Flora of Acanthaceae of Iguaçu National Park, Paraná, Brazil - Hammes, Janaine Kunrath [UNESP]; Silva, Marizete Gonçalves Da; Kameyama, Cíntia; Temponi, Lívia Godinho (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2021)
Species of Acanthaceae are predominantly associated with conserved forest environments such as Iguaçu National Park (PARNA Iguaçu), which is composed of Semideciduous Seasonal Forest and Araucaria forest. The aim of this work was to perform a floristic study of Acanthaceae of PARNA Iguaçu, with botanical illustrations, an identification key and descriptions of the species. Collections were carried out monthly from August 2015 to July 2016, in the areas of Céu Azul, Capanema and Foz do Iguaçu. The individuals collected were deposited in the UNOP herbarium and the specimens present in the herbaria EVB, HCF, MBM and UNOP, as well as in the virtual herbaria Reflora and SpeciesLink, were analyzed. A total of 13 native species were recorded from Atlantic Forest, distributed in seven genera. Justicia was the most representative, with five species. In all, 12 new records were made for PARNA Iguaçu, of which eight are new records for Semideciduous Seasonal Forest. Of the species found, three are threatened with extinction, one of which is considered vulnerable and two are categorized as endangered, which reinforces the role of PARNA Iguaçu in in-situ conservation in the state of Paraná.

As espécies de Acanthaceae são predominantemente associadas a ambientes florestais conservados como o Parque Nacional do Iguaçu, composto pelas Florestas Estacional Semidecidual e Ombrófila Mista. Este trabalho teve como objetivo realizar a flora de Acanthaceae do PARNA Iguaçu, com ilustrações botânicas, chave de identificação e descrições das espécies. Para isso foram realizadas coletas mensais de agosto de 2015 a julho de 2016 nas áreas de Céu Azul, Capanema e Foz do Iguaçu. Os indivíduos coletados foram depositados no herbário UNOP e os espécimes presentes nos herbários EVB, HCF, MBM e UNOP, assim como nos herbários virtuais Reflora e SpeciesLink, foram analisados. Foram encontradas 13 espécies nativas da Mata Atlântica, distribuídas em sete gêneros, sendo Justicia o mais representativo, com cinco espécies. Foram registradas 12 novas ocorrências para o Parque Nacional do Iguaçu, das quais oito são novos registros para Floresta Estacional Semidecidual. Dentre as espécies encontradas, três são ameaçadas de extinção, sendo uma categorizada como vulnerável e duas em perigo de extinção, o que reforça o papel do PARNA Iguaçu na conservação in-situ no estado do Paraná.
Keywords: Araucaria Forest; Justicia; Ruellia; Semideciduous Seasonal Forest; Streblacanthus; Floresta Ombrófila Mista; Justicia; Ruellia; Floresta Estacional Semidecidual; Streblacanthus